Truly sedentary? The multi-range tactic as a response to resource heterogeneity and unpredictability in a large herbivore - Couriot, Ophélie; Hewison, A J Mark; Saïd, Sonia; Cagnacci, Francesca; Chamaillé-Jammes, Simon; Linnell, John D C; Mysterud, Atle; Peters, Wibke; Urbano, Ferdinando; Heurich, Marco; Kjellander, Petter; Nicoloso, Sandro; et al. (Oecologia, 2018)
Much research on large herbivore movement has focused on the annual scale to distinguish between resident and migratory tactics, commonly assuming that individuals are sedentary at the within-season scale. However, apparently sedentary animals may occupy a number of sub-seasonal functional home ranges (sfHR), particularly when the environment is spatially heterogeneous and/or temporally unpredictable. The roe deer (Capreolus capreolus) experiences sharply contrasting environmental conditions due to its widespread distribution, but appears markedly sedentary over much of its range. Using GPS monitoring from 15 populations across Europe, we evaluated the propensity of this large herbivore to be truly sedentary at the seasonal scale in relation to variation in environmental conditions. We studied movement using net square displacement to identify the possible use of sfHR. We expected that roe deer should be less sedentary within seasons in heterogeneous and unpredictable environments, while migratory individuals should be seasonally more sedentary than residents. Our analyses revealed that, across the 15 populations, all individuals adopted a multi-range tactic, occupying between two and nine sfHR during a given season. In addition, we showed that (i) the number of sfHR was only marginally influenced by variation in resource distribution, but decreased with increasing sfHR size; and (ii) the distance between sfHR increased with increasing heterogeneity and predictability in resource distribution, as well as with increasing sfHR size. We suggest that the multi-range tactic is likely widespread among large herbivores, allowing animals to track spatio-temporal variation in resource distribution and, thereby, to cope with changes in their local environment.
Keywords: Roe deer; teritoriální chování; Deer; Plasticity; vysoká zvěř; Herbivory; roční období; Animals; Migration; Sub-seasonal functional home range; Homing Behavior; Residency; zvířata; Evropa; Seasons; býložravci; Europe